Risk of stroke and retinopathy during GLP-1 receptor agonist cardiovascular outcome trials: An eight RCTs meta-analysis - Wei, Jinjing; Yang, Bing; Wang, Ruxin; Ye, Haowen; Wang, Ying; Wang, Lihong; Zhang, Xiaofang (Frontiers in Endocrinology, 2022)
Abstract Purpose To explore the risk of stroke (including ischemic and hemorrhagic stroke) in patients with type 2 diabetes treated with glucagon-like peptide 1 receptor agonist (GLP-1RA) medication according to data from the Cardiovascular Outcome Trial（CVOT）. Methods Randomized controlled trials (RCT) on GLP-1RA therapy and cardiovascular outcomes in type 2 diabetes mellitus patients published in full-text journal databases such as MEDLINE (via PubMed), Embase, Clinical Trials.gov, and the Cochrane Library from establishment to May 1, 2022 were searched. We assessed the quality of individual studies by the Cochrane risk-of-bias algorithm . RevMan 5.4.1 software was use for calculating meta analysis. Results A total of 60,081 randomized participants were included in the data of these 8 GLP-1RA cardiovascular outcomes trials. Pooled analysis reported statistically significant effect on total stroke risk[RR=0.83， 95%CI(0.73，0.95)，p=0.005], and its subtypes such as ischemic Stroke [RR=0.83， 95%CI(0.73，0.95)，p=0.008] from treatment with GLP-1RA versus placebo，and have no significant effect on the risk of hemorrhagic stroke[RR=0.83， 95%CI(0.57，1.20)，p=0.31] and retinopathy [RR=1.54， 95%CI(0.74，3.23)，p=0.25] Conclusion GLP-1RA significantly reduces the risk of ischemic stroke in type 2 diabetic patients with cardiovascular risk factors.